Plant protection product residues in plant pollen and nectar: A review of current knowledge - Zioga, Elena; Kelly, Ruth; White, Blánaid; Stout, Jane C. (Environmental research, 2020)
Exposure to Plant Protection Products, PPPs, (fungicides, herbicides and insecticides) is a significant stressor for bees and other pollinators, and has recently been the focus of intensive debate and research. Specifically, exposure through contaminated pollen and nectar is considered pivotal, as it presents the highest risk of PPP exposure across all bee species. However, the actual risk that multiple PPP residues might pose to non-target species is difficult to assess due to the lack of clear evidence of their actual concentrations. To consolidate the existing knowledge of field-realistic residues detected in pollen and nectar directly collected from plants, we performed a systematic literature review of studies over the past 50 years (1968–2018). We found that pollen was the matrix most frequently evaluated and, of the compounds investigated, the majority were detected in pollen samples. Although the overall most studied category of PPPs were the neonicotinoid insecticides, the compounds with the highest median concentrations of residues in pollen were: the broad spectrum carbamate carbofuran (1400 ng/g), the fungicide and nematicide iprodione (524 ng/g), and the organophosphate insecticide dimethoate (500 ng/g). In nectar, the highest median concentration of PPP residues detected were dimethoate (1595 ng/g), chlorothalonil (76 ng/g), and the insecticide phorate (53.5 ng/g). Strong positive correlation was observed between neonicotinoid residues in pollen and nectar of cultivated plant species. The maximum concentrations of several compounds detected in nectar and pollen were estimated to exceed the LD50s for honey bees, bumble bees and four solitary bee species, by several orders of magnitude. However, there is a paucity of information for the biggest part of the world and there is an urgent need to expand the range of compounds evaluated in PPP studies. [Display omitted]